The Budhikhiamari Model of Participatory Management of the forest Eco-system in Orissa - Mishra, G. (Indian Forester, 1994)
To save the forests from illicit removal of fuel, fodder, timber and minor forest product by the near villagers,the Forest Department played a novel task. The villagers were motivated in active Conservtion of the forests. This new and successful model of participatory management has been adopted by 79 villages.